Loss to Follow-up Pattern in TB Patients in Rawalpindi, Pakistan (Journal of Medicine, 2015)
Background: Tuberculosis is a serious global public health, social and economical problem that affects millions of people particularly in low income countries. The aim of this study was to see the loss to follow up pattern in Tuberculosis patients in district Rawalpindi, Pakistan. Materials and method: A cross-sectional study was conducted in district Rawalpindi between August and October 2010. All sputum smear positive Tuberculosis patients diagnosed and treated in public sector, urban and rural diagnostic centers of the district Rawalpindi during the year 2008 were included in the study.All cases other (smear negative pulmonary and extra-pulmonary) than sputum smear positive and all private hospitals were excluded. Results: A total of 451 patients were enrolled in the study. Majority of the patients (89.6%) were provided with the treatment support. Geographically dropout rate was observed higher in urban patients than in rural 18.7% vs. 10.5%. On the other hand by patient gender, drop out was seen more in male patients than in females 16.5% vs. 13.1%. By patients age groups, interestingly patients under the childhood age group all the patients completed the treatment while drop out was observed more in older age group. Conclusions: Loss to follow up pattern was seen more in urban patients, by gender more in male patients and by age groups observed more in older patients.DOI: http://dx.doi.org/10.3329/jom.v16i1.22374 J MEDICINE 2015; 16 : 10-13